Pemberdayaan Masyarakat Melalui Pendidikan Kewarganegaraan Dalam Meningkatkan Partispasi Sosial - Destalenta Trisna Laoli; Merlis Telaumbanua (CV. SINAR HOWUHOWU, 2025)
Citizenship education plays a crucial role in shaping social awareness and participation within communities. This article discusses efforts to empower communities through citizenship education as a strategy to enhance social participation in community life. This empowerment includes providing knowledge, skills, and understanding of the rights and responsibilities of responsible citizens. Through citizenship education, communities are expected to actively participate in decision-making processes, social activities, and maintaining social harmony. Moreover, increased social participation also contributes to sustainable development and the strengthening of democracy at both local and national levels. This research employs a qualitative method with a case study approach in several communities. The findings indicate that community empowerment through citizenship education can enhance social awareness, solidarity, and community engagement in social activities. Thus, citizenship education functions not only as a means of formal learning but also as an effective empowerment tool for creating participatory and resilient communities.